Behavioural pattern of mobile phone usage while driving among educated young adults in Klang Valley - Md. Isa, Khairil Anuar; Masuri, Mohamad Ghazali; Azmi, Alia; Abd. Aziz, Nor Azimah; Md. Isa, Nurun Nadhirah; Hazali, Norazlanshah; Majid, Norhaini (Faculty of Architecture, Planning & Surveying, UiTM, 2012)
Introduction: Students who drive and using mobile phones become a common sight these days. This causes lack of coordination contributing patterns of mobile phone usage while driving among educated young adults. Methods: A cross sectional study was conducted among students in Klang Valley whom participated voluntarily. Results & conclusion: Study found 66.6% of participants used mobile phone while driving and male driver were found to have used phones more often while driving on urban road.